1989
DOI: 10.1002/aic.690350902
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria for supercritical fluid process design

Abstract: Supercritical fluids (SCF's) are powerful solvents with many unique properties. They have great potential for many extraction processes, but reliable and versatile mathematical models of the phase equilibrium thermodynamics are needed for their use in process design and economic feasibility studies. This paper reviews existing experimental data and analytical methods and attempts to delineate their strengths and limitations. Also discussed are new data needs and possible new directions for a better fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
209
0
3

Year Published

1992
1992
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 323 publications
(213 citation statements)
references
References 158 publications
(127 reference statements)
1
209
0
3
Order By: Relevance
“…In the latter studies, the observed spectral shift was more than expected based on the McRae theory (56,57), this was attributed to cluster formation. In other studies, Brennecke and Eckert (5,31,44,45) examined the fluorescence of pyrene in supercritical CQ2, C 2 H^y and CHF 3 . Steady-state emission spectra were used to show density augmentation near the critical point.…”
Section: Spectroscopic Investigations Of Supercritical Fluidsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the latter studies, the observed spectral shift was more than expected based on the McRae theory (56,57), this was attributed to cluster formation. In other studies, Brennecke and Eckert (5,31,44,45) examined the fluorescence of pyrene in supercritical CQ2, C 2 H^y and CHF 3 . Steady-state emission spectra were used to show density augmentation near the critical point.…”
Section: Spectroscopic Investigations Of Supercritical Fluidsmentioning
confidence: 99%
“…The general conclusion from these studies is that there is local density augmentation (i.e., solvent clustering) about the solute near the critical point. In addition, it has been suggested that there is enhanced solute-solute interactions near the critical point (5,31,(43)(44)(45).…”
mentioning
confidence: 99%
See 3 more Smart Citations